MONITORING CUACA BERBASIS ARDUINO UNO - Fauzan Alaudin Hadi; Muhammad Rif’an; Mochammad Djaohar (Journal of Electrical Vocational Education and Technology, 2016)
Abstract This research aims to create a monitoring tool based weather arduino uno in order to produce data of wind, precipitation, temperature, and light intensity to be used as a reference whether or not an area to be built hybrid power plant. This research was conducted in the building innovation center LIPI, Cibinong, Bogor, West Java in March 2016 - July 2016. The method used is an experimental method that connects the sensor with arduino uno, then connected again to the server computer by using radio frequency signals using the XBee. Steps to be done is to make the program a tool, and then create a hardware appliance, create an interface with visual basic. Tests performed on hardware and software. From the test results, testing both hardware and software managed to work well and is able to generate data in the form are the wind speed reached a daily average of 6.2 m / s, the average rainfall reached 59.95 mm / day, the average temperature reached 26.71 ℃ per day, and the intensity of light that is able to produce the rated voltage -rata up 18,5v. The data shows that weather conditions in the study has good potential to build hybrid power plant. Abstrak Penelitian ini bertujuan untuk membuat alat monitoring cuaca berbasis arduino uno dalam rangka menghasilkan data angin, curah hujan, suhu, dan intensitas cahaya yang akan digunakan sebagai acuan layak atau tidaknya suatu daerah untuk dibangun pembangkit listrik hybrid. Penelitian ini dilaksanakan di gedung pusat inovasi LIPI, Cibinong, Bogor, Jawa Barat pada bulan maret 2016 – Juli 2016. Metode yang digunakan adalah metode eksperimen yaitu menghubungkan sensor dengan arduino uno, lalu dihubungkan lagi ke komputer server dengan menggunakan sinyal radio frekuensi menggunakan XBee. Langkah yang dilakukan adalah membuat program alat, lalu membuat hardware alat, membuat interface dengan visual basic. Pengujian dilakukan pada hardware dan software. Dari hasil pengujian, baik hardware maupun software berhasil bekerja dengan baik dan mampu menghasilkan data berupa kecepatan angin rata-rata perhari mencapai 6,2 m/s, curah hujan rata-rata mencapai 59,95 mm/hari, suhu rata-rata mencapai 26,71 perhari, dan intensitas cahaya yang mampu menghasilkan tegangan rata-rata hingga 18,5v.